Nine new species and one new name in Maxillaria (Orchidaceae) - Bennett, David E.; Christenson, Eric A. (Phytotaxa, 2009)
Nine new species of Maxillaria from Peru are described and illustrated, one based on a previously published variety: M. canarina, M. coniformis, M. deniseae, M. dichaeoides, M. flabellata, M. hajekii, M. leucopurpurea, M. striolata, and M. visseri. In addition, the new name M. calendulina is proposed for the Colombian M. aurantiaca Schlechter (1924: 87).